2021
DOI: 10.3390/molecules26247667
|View full text |Cite
|
Sign up to set email alerts
|

Scalarane Sesterterpenoids with Antibacterial and Anti-Proliferative Activities from the Mushroom Neonothopanus nambi

Abstract: Seven undescribed scalarane sesterterpenoids, nambiscalaranes B–H (1–7), together with two known compounds, nambiscalarane (8) and aurisin A (9) were isolated from the cultured mycelium of the luminescent mushroom Neonothopanus nambi. Their structures were elucidated by thorough analysis of their 1D and 2D NMR spectroscopic data. The absolute configurations of 1–8 were determined by electronic circular dichroism (ECD) calculations and optical rotation measurements. The isolated sesterterpenoids were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The anti-proliferative effect on cancer cells was evaluated by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay [2]. Cells (8 × 10 3 cell/well) were seeded onto 96-well plates and incubated for 24 h to allow adherence.…”
Section: Anti-proliferative Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-proliferative effect on cancer cells was evaluated by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay [2]. Cells (8 × 10 3 cell/well) were seeded onto 96-well plates and incubated for 24 h to allow adherence.…”
Section: Anti-proliferative Assaymentioning
confidence: 99%
“…As part of our continuous efforts to identify new bioactive metabolic scaffolds from plants and fungi growing in Thailand 1 , 2 , 3 , 4 , we decided to investigate Acronychia pedunculata (L.) Miq. A. pedunculata .…”
Section: Introductionmentioning
confidence: 99%
“…R.H. Petersen & Krisai and deposited at DSMZ Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH under the accession number DSM 24013. Previous researchers have shown that N. nambi produced many different bioactive secondary metabolites exhibiting nematicidal activity against root-knot nematode Meloidogyne incognita ( Bua-art et al, 2011 ), cytotoxicity against cancer cells ( Kanokmedhakul et al, 2012 , Boueroy et al, 2020 , Boueroy et al, 2021 , Wisetsai et al, 2021 ), and antimalarial, antimycobacterial ( Kanokmedhakul et al, 2012 ) and antibacterial ( Sangsopha et al, 2020 , Wisetsai et al, 2021 ) activities. In this study, a bioactive compound was isolated from N. nambi DSM 24013 and evaluated for the first time for inhibitory effects against different reference and clinical MRSA strains, as well as presence of synergistic effects when combined with other antistaphylococcal antibiotics before proceeding to understand its mechanism/s of action in future studies.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Since then, more than two hundred scalaranes have been isolated and attracted the attention and research interest of many scientists in the fields of medicinal chemistry and organic synthesis due to their unique structure cores with many different kinds of oxygen-containing functional groups, [3] as well as their diverse biological activities, such as cytotoxicity, antibacterial, anti-inflammatory, antifungal, antitumor, antifeedant, antiviral, antimicrobial, anti-HIV, antitubercular, antifouling, suppression of platelet aggregation, and activation of nerve growth factor synthesis. [4][5][6][7][8] Scalarane-type sesquiterpenoids from marine organisms have been the subject of several review articles. [9][10][11] Structurally, scalarane-type sesquiterpenoids were mainly composed of two types, including homoscalaranes (methylation at C-23 or C-24) and bishomoscalaranes (methylations at both C-23 and C-+ These authors contribute equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…The first member of this family, scalarin, was isolated from Mediterranean sponge Cacospongia scalaris by Fattorusso in 1972 [2] . Since then, more than two hundred scalaranes have been isolated and attracted the attention and research interest of many scientists in the fields of medicinal chemistry and organic synthesis due to their unique structure cores with many different kinds of oxygen‐containing functional groups, [3] as well as their diverse biological activities, such as cytotoxicity, antibacterial, anti‐inflammatory, antifungal, antitumor, antifeedant, antiviral, antimicrobial, anti‐HIV, antitubercular, antifouling, suppression of platelet aggregation, and activation of nerve growth factor synthesis [4–8] …”
Section: Introductionmentioning
confidence: 99%